THE EFFECT OF HIGH DIETARY LEVELS OF PHOSPHORUS ON THE PERFORMANCE OF LAYING HENS - A. Fahad, M.; Kassab, A. (The Iraqi Journal of Veterinary Medicine, 1988)
One hundred and twenty Hisex Brown commercial layers at the age of 40 weeks were divided into 3 groups each was subdivided into 4 replicants. Each group was given one of three diets contained either 0.54, 1.04 or 1.54% available phosphorus and 3.0% calcium for one month. Egg production was recorded, and eggs and shells were weighed. Group 2 produced more egg (12.18 egg/day) than group 1 (9.31 egg/day) and group 3 (9.3 egg/day). Groups received higher percentage of available phosphorus in their diets produced heavier eggs (65.14, 67.67 and 68.28 g/egg respectively). Egg shell weight was increased accordingly when available phosphorus in the diet was raised (7.88, 8.85 and 9.0 g/egg respectively). It was concluded that the available phosphorus in the diets contained 3.0% calcium cam be increased from 0.5% to 1.0% with beneficial results on egg production and egg weight